The Digital Music Market: a study of Brazilian consumers’ behavior - Capelli Martins, João Paulo; Slongo, Luiz Antonio (Review of Business Management, 2014)
The convergence between technology, the Internet and music brought about great challenges to the recording industry worldwide. Despite digital music’s revenue growth, the music industry has declined significantly over recent years. To attract new customers and compete with other ways of getting music on the network, record companies and on-line music providers must figure out who their potential customers are. The goal of this study was to explore and describe the characteristics and behavior of digital music users, as well as of those who are willing to pay or unwilling to use this service, in order to fully understand this market’s context. These are the study’s main findings: 1) 88% of the sample of Brazilian Internet users are also digital music users; 2) their profile is significantly related to the profile of Internet usage (social networking and entertainment); 3) non-users fail to use digital music mainly due to lack of knowledge on how to do it; 4) 66.4% intend to pay for digital music; 5) they share one characteristic: they frequently shop online; 6) people who are willing to pay for digital music receive the difference between legal and illegal music, and do not value the Internet much. We hope this study will promote efficient, customer-oriented marketing actions.